Law, Money Politics, and Public Preferences in Choosing Regional Head Candidates in Ternate City, Indonesia - Irham Rosyidi; Mahmud Hi Umar; Kachippa Suvirat; Aslan Rumicovic (Fakultas Hukum Universitas Muhammadiyah Magelang, 2022)
In Indonesia, there are still people who are registered as permanent voters but have not exercised their voting rights. This study aims to analyze people's preferences in the implementation of simultaneous regional head elections in Ternate City, as well as the efforts made by the General Election Supervisory Agency to suppress the practice of money politics in the 2024 Simultaneous Regional Head Elections in Ternate City. This research used the anthropological approach which studied the behavior or preferences of society during the simultaneous election of regional heads in Ternate City. This study used a sociological research method, where the author carried out direct observations or research in the field to obtain accurate data to answer the research problems. Results showed that voters in Ternate City tend to become irrational voters during simultaneous regional head elections and most respondents (40%) stated that they chose candidate pairs based on cash compensation, projects, and positions. Then, the General Election Supervisory Agency makes efforts to suppress money politics in the 2014 Simultaneous Regional Head Election in Ternate City by applying the participatory monitoring movement.